2005
DOI: 10.1139/e04-084
|View full text |Cite
|
Sign up to set email alerts
|

The McAbee flora of British Columbia and its relation to the Early-Middle Eocene Okanagan Highlands flora of the Pacific Northwest

Abstract: Megafossils and pollen data are used to compare the flora found at the McAbee site, located near the town of Cache Creek, British Columbia, to six other well-collected Eocene lacustrine floras of Washington and western British Columbia. A diverse flora is found at McAbee consisting of at least 87 taxa. Gymnosperms are common, including sixteen separate species, 14 conifers and two ginkgos. A minimum of 67 angiosperm genera are represented in the flora, many yet to be described. The dominant dicotyledonous elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…The McAbee site is dominated by numerous conifers, Fagus leaves and nuts (Manchester & Dillhoff 2004), fruits and leaves of Ulmus (Denk & Dillhoff 2005), Betula, and Alnus (Dillhoff et al 2005). This site contrasts with Quilchena, which is considered the "warmest and wettest" of the Okanogan Highlands sites (Mathewes & Greenwood 2007).…”
Section: The Okanogan Highlandsmentioning
confidence: 91%
“…The McAbee site is dominated by numerous conifers, Fagus leaves and nuts (Manchester & Dillhoff 2004), fruits and leaves of Ulmus (Denk & Dillhoff 2005), Betula, and Alnus (Dillhoff et al 2005). This site contrasts with Quilchena, which is considered the "warmest and wettest" of the Okanogan Highlands sites (Mathewes & Greenwood 2007).…”
Section: The Okanogan Highlandsmentioning
confidence: 91%
“…1, 3), about 85 km north of Kamloops, British Columbia (Arnold 1955a(Arnold , 1955bBrown 1962;Wolfe and Tanai 1987;Gooch 1992;Wolfe et al 1998Wolfe et al , 2000McClain and Manchester 2001;Denk and Dillhoff 2005;Dillhoff et al 2005;Villeneuve and Mathewes 2005;Feng and Poulsen 2016). It is likely the various authors citing either Chu Chua or Joseph Creek refer to multiple separate outcrops exposed near the villages by the same names, which are about 15 km apart along the North Thompson River, north of Kamloops on Provincial Highway 5 (Fig.…”
Section: Horsefly Rivermentioning
confidence: 99%
“…(Denk and Dillhoff 2005), Trochodendron drachukii and associated leaves , and a reproductive structure of unknown affinities named Dillhoffia cachensis (Manchester and Pigg 2008). Both Greenwood et al (2005) and Dillhoff et al (2005Dillhoff et al ( , 2013 provided paleoclimate reconstructions for McAbee (see Gushulak et al 2016), and both Dillhoff et al (2005) and Moss et al (2005) presented pollen count data that indicated a diverse flora. While primarily focused on insects in his study of McAbee, Archibald et al (2010) used rarefaction analysis of a small collection (<200 leaves) to show plant diversity in the Early Eocene comparable to tropical rainforest sites, corroborating an extensive and detailed assessment of insect diversity.…”
Section: Horsefly Rivermentioning
confidence: 99%
See 2 more Smart Citations